A délvidéki régióközpontok - Arad, Temesvár és Szeged - ipara a dualista korszakban - Gulyás, László (Közép-Európai Közlemények, 2010)
Some searchers –József Tóth, Pál Beluszky, István Süli Zakar and Gábor Csüllög –came to the conclusion independently from each other that in the 19 century important region-commencements came to being within de framework of the Austro-Hungarian Monarchy, out of which some regions could have been formed in case of untroubled development. But the development of the expanding regions of the Austro–Hungarian Monarchy has been hindered by the change of state structures at Treaty of Trianon. One of the expanding region was „Délvidék”, which consists of whole area Bodrog, Torontál, Temes és Krassó-Szörény counties and small parts of Csongrád, Csanád and Arad counties. The potential region centers of Délvidék were Arad, Temesvár and Szeged. Our study is aimed to com-pare the one dimension –the industry –of these three region centers.